The impact of self help groups in facilitating rural development: case study of Hurumutumbu rural community, Mutoko ward 29 - Pawandiwa, Perfect (Midlands State University, 2017)
The study looks at the impact of SHGs in facilitating rural development. Rural development is mainly on the up gradation of socio-economic, technological, environmental and financial status of the rural folks. The study is thus exhibiting whether SHGs has been a panacea for rural development or vice versa. The study also looks at the nature and operation of SHGs and so is the constraints faced by this concept. In this case, the study made use of mixed research methodology for gathering information from the area of study, that is, Hurumutumbu rural community. KIs were also interviewed in order to generate quality information. The research methods complement each other hence informative data is obtained from the field. The study in its entirety confirmed that SHGs are a cure all solution to rural poverty and they facilitate rural development. This is aggravated with the social, economic, educational, environmental, technological and financial indicators. The study recommends the government to embark on infrastructural development in rural areas to ensure that SHGs are serviced. This has the essence of creating market linkages and centralization of services.